Hypoxic training methods for improving endurance exercise performance - Sinex, J. A.; Chapman, R. F. (Journal of Sport and Health Science, 2015)
Endurance athletic performance is highly related to a number of factors that can be altered through altitude and hypoxic training including increases in erythrocyte volume, maximal aerobic exercise capacity, capillary density, and economy. Physiological adaptations in response to acute and chronic exposure to hypoxic environments are well documented and range from short-term detrimental effects to longer-term adaptations that can improve performance at altitude and in sea-level competitions. Many altitude and hypoxic training protocols have been developed, employing various combinations of living and training at sea-level, low, moderate, and high altitudes and utilizing natural and artificial altitudes, with varying degrees of effectiveness. Several factors have been identified that are associated with individual responses to hypoxic training, and techniques for identifying those athletes most likely to benefit from hypoxic training continue to be investigated. Exposure to sufficiently high altitude (2000-3000m) for more than 12h/day, while training at lower altitudes, for a minimum of 21 days is recommended. Timing of altitude training related to competition remains under debate, although general recommendations can be considered.